Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/vop.12123
|View full text |Cite
|
Sign up to set email alerts
|

Ocular findings and reference values for selected ophthalmic diagnostic tests in the macaroni penguin (Eudyptes chrysolophus) and southern rockhopper penguin (Eudyptes chrysocome)

Abstract: Cataracts were the most common finding, present in 64% of Macaroni Penguins, and 68% of Rockhopper Penguins. There were anterior segment anomalies in all eyes with cataracts consistent with lens-induced uveitis. The mean modified PTT for the Macaronis was 24.7 ± 6.37 mm/15 s and 25.1 ± 7.07 mm/15 s in the Rockhoppers. The mean STT value for the Macaronis was 12.1 ± 5.43 mm/min and 11.0 ± 3.96 mm/min in the Rockhoppers. Mean intraocular pressure (IOP) for the Macaronis was 21.9 ± 7.05 mmHg measured by applanati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
70
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(92 citation statements)
references
References 54 publications
14
70
8
Order By: Relevance
“…18 The effect of age was not assessed in this study because precise determination of age was not possible in our study population. In Humboldt penguins, 7 macaroni penguins, 8 rockhopper penguin, 8 Screech owls, 10 vultures, 12 ostriches, 13 and American flamingos, 21 the age and gender did not alter results of STT and/or IOP in studied animals. But as determined by Reuter and colleagues in some birds of prey (northern goshawks, common buzzards, and common kestrels), 18 younger birds had lower IOP values than did older birds.…”
Section: Discussionmentioning
confidence: 47%
“…18 The effect of age was not assessed in this study because precise determination of age was not possible in our study population. In Humboldt penguins, 7 macaroni penguins, 8 rockhopper penguin, 8 Screech owls, 10 vultures, 12 ostriches, 13 and American flamingos, 21 the age and gender did not alter results of STT and/or IOP in studied animals. But as determined by Reuter and colleagues in some birds of prey (northern goshawks, common buzzards, and common kestrels), 18 younger birds had lower IOP values than did older birds.…”
Section: Discussionmentioning
confidence: 47%
“…Although this test is well tolerated by birds (Bliss et al 2015), low reproducibility has been reported in large Psitacciformes (Holt et al 2006), and better PRT reproducibility on A. ventralis (Storey et al 2009). …”
Section: Discussionmentioning
confidence: 94%
“…Factors such as season, geography, nutrition, population density and contact with other animals can influence these results (Swinger et al 2009), highlighting the importance of determining the local flora in accordance with the region. Knowledge of specific normal ocular findings for each species, as well as reference values for diagnostic tests, is essential for comparative veterinary ophthalmology (Bliss et al 2015).…”
Section: Discussionmentioning
confidence: 99%